The Extension of Wittgenstein’s Language Games: Schema Games - Hans Lenk (Selected Topics in Humanities and Social Sciences Vol. 2, 2021)
Wittgenstein’s idea of “language games” is generalized to “schema games” and - accordíng to the author’s methodological scheme interpretationism - be thus applied to a universal epistemological approach. That will also integrate extant natural science and neuroscience results and hypotheses as well as meta-theoretically transcend the terminologically all too narrow “lingualistic” interpretations of representation, cognition and action.